Improving waste-to-energy process by co-digestion of exhausted coffee biowaste and WWTP sludge. (October 2017) - Carvalho, Ana; Fragoso, Rita; Duarte, Elizabeth
Abstract: The purpose of this study is to investigate the effects of using pre-treated exhausted coffee biowaste (ECB) as a co-substrate to optimize sewage sludge (SS) biogas production. The trials were conducted in semi-continuous mode at mesophilic conditions (36 ± 1ºC) with a Hydraulic Retention Time of 17 days and an average organic loading rate (0.94 ± 0.05 g VS Lreactor .day -1 ). An anaerobic co-digestion trial (T1) was assessed using a feeding mixture with a ratio of SS (80 %) and LECB (20%), v:v, and compared against a reference scenario (T0). Results showed that the addition of the co-substrate had a significant influence on specific methane production (3 times higher) and biogas quality (12% higher), which is a feasible strategy towards self-sufficient wastewater treatment plant. Furthermore, the stability along assays was ensured monitoring the digestate characteristics (pH, electrical conductivity, total alkalinity and ammonia content) and the specific energy loading rate.